Management of Chronic Obstructive Pulmonary Disease in Vietnam during the COVID-19 Period: Current Situation and Challenges - Thuy Thanh Phan; Giap Van Vu; Chau Quy Ngo (Tuberculosis and Respiratory Diseases)
Background To assess the alterations in exacerbation rates, other clinical outcomes, and to identify persistent challenges in the management of chronic obstructive pulmonary disease (COPD) in Vietnamese COPD management units (CMUs). Methods A multi-center, prospective cohort study was conducted on COPD within the CMUs of three study sites. The primary endpoint was exacerbation frequency. Data on demographic and clinical characteristics were collected at the initiation of the study. Participants were followed for 12 to 15 months after enrollment. Results Throughout the follow-up period, a decrease was noted in the prevalence of patients requiring hospitalization (from 42.3% to 34.4%) and intensive care unit/emergency department admissions (from 5.7% to 0.6%). The annual rates of exacerbation and hospitalization were 0.75±0.89 and 0.56±0.70, respectively. Factors such as symptom severity, degree of airflow obstruction, and body mass index were associated with increased exacerbation frequency and elevated annual exacerbation rates. Our findings underscore the complexities and obstacles encountered in managing COPD during the coronavirus disease 2019 (COVID-19) pandemic, including the rise in smoking prevalence, inadequate testing rates, and non-compliance with established treatment guidelines. Conclusion Our study elucidates the challenges and difficulties in managing COPD amidst the COVID-19 pandemic, highlighting issues such as increased smoking rates, insufficient testing, and deviations from established therapeutic guidelines. These insights lay the groundwork for future intervention strategies and policy enhancements.